Naturally Available Transport Medium For Avulsed Teeth- A Review - Ramya Chellammal1 , Jeevarathan J2 , PonnuduraiArangannal3 , Vijayakumar M4 , Amudha S5 , Aarthi J6 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Tooth avulsion or exarticulation is a traumatic injury of dental tissue characterised by complete displacementof the tooth out of its socket. Successful treatment outcome is dependent on the survival of the viableperiodontal ligament cells attached to the tooth root surface. This review discusses various storage/ transportmedia for avulsed tooth obtained from natural sources. The knowledge of availability and accessibilityof such natural storage media would increase the awareness among the healthcare providers and wouldtherefore improve the prognosis of the treatment protocol by reducing extra-oral dry time of the avulsedtooth